Answer:
(-3,1)
Step-by-step explanation:
Equation: 3x - 4y = -13
- We are given the clue : x = 2y - 5
- Substitution Method means :
- We can plug 2y-5 in for x (because x = 2y - 5)
3. Plug X into the equation (3x - 4y = -13):
- 3(2y-5) - 4y = -13
- Distribute (multiply the terms 2y and -5 by 3):
- 6y - 15 is the new term
- Write the rest of the equation
- 6y - 15 - 4y = -13
- Simplify (add the y terms first)
- (6y) + (-4y) will equal 2y
- Now we have
- 2y - 15 = -13
- Add 15 to both sides
- 2y = -13 + 15
- Simplify
- 2y = 2
- Divide both sides by 2, and you will get:
y = 1
4. We plugged x into the equation to get y, now we can plug y into the equation to get x:
- 3x - 4(1) = -13
- 4(1) will equal 4 so we have :
- 3x - 4 = -13
- Add 4 to both sides to get :
- 3x = -9
- Divide both sides by 3 to get :
X = -3
Now we have (-3, 1) , Good job! I hope this helps